Tax Avoidance through Transfer Pricing: How Foreign Ownership Moderates the Effects - Oktaviano, Benny; Wulandari, Dian; Masitoh, Siti (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
This study investigates the impact of transfer pricing on tax avoidance and explores how foreign ownership moderates this relationship. The objective is to understand whether transfer pricing strategies lead to increased tax avoidance and how foreign ownership influences this effect. Using panel least squares regression, the results show a significant positive relationship between transfer pricing and tax avoidance, with foreign ownership amplifying this effect. Firms with higher foreign ownership tend to leverage transfer pricing strategies more effectively to minimize tax liabilities. These findings align with existing literature on multinational corporations' tax strategies and suggest the need for stricter regulatory frameworks to mitigate aggressive tax avoidance. The study's limitations include a narrow sample and time frame, with recommendations for future research to expand the scope and examine additional moderating factors.